From a lab in Luxembourg to satellites in South Sudan - Donven, M; Hall, M (Refugee Studies Centre, University of Oxford, 2012)
A new communications platform for use in humanitarian emergencies made its debut in January 2012 in South Sudan, and is now being deployed elsewhere. Emergency.lu aims to be a global inter-agency tool.